Prevention of TB using rifampicin plus isoniazid reduces nevirapine concentrations in HIV-exposed infants. (16th April 2017) - McIlleron, Helen; Denti, Paolo; Cohn, Silvia; Mashabela, Fildah; Hoffmann, Jennifer D.; Shembe, Saba; Msandiwa, Regina; Wiesner, Lubbe; Velaphi, Sithembiso; Lala, Sanjay G.; Chaisson, Richard E.; Martinson, Neil; et al.
Abstract: Background: Newborns of HIV-infected mothers are given daily doses of nevirapine to prevent HIV-1 acquisition. Infants born to mothers with TB should also receive TB preventive therapy. TB preventive regimens include isoniazid for 6 months or rifampicin plus isoniazid for 3 months (RH preventive therapy). The effect of concomitant RH preventive therapy on nevirapine concentrations in infants is unknown. Patients and methods: Tshepiso was a prospective case–control cohort study of pregnant HIV-infected women with and without TB whose newborn infants received standard doses of nevirapine for HIV prophylaxis. Infants born to mothers with TB also received RH preventive therapy. Infant plasma nevirapine concentrations were measured at 1 and 6 weeks. The effects of RH preventive therapy on nevirapine disposition were investigated in a population pharmacokinetic model. Results: Of 164 infants undergoing pharmacokinetic sampling, 46 received RH preventive therapy. After adjusting for weight using allometric scaling, the model estimated a 33% reduction in nevirapine trough concentrations with RH preventive therapy compared with TB-unexposed infants not receiving concomitant rifampicin and a 30% decline in trough concentrations in a typical infant between day 7 and 35 post-partum. Conclusions: Rifampicin-based TB preventative treatment reduces nevirapine concentrations significantly in HIV-exposed infants. Although the nevirapine exposures required to prevent HIV acquisition in breastfeeding infants are undefined, given the potential risks associated with underdosing nevirapine in this setting, it is prudent to avoid rifampicin-based preventive therapy in HIV-exposed children receiving prophylactic nevirapine.